Atypical Muscular Sarcoidosis Involvement Revealed by 18F-FDG PET/CT - Lucinian, Yousif A.; Martineau, Patrick; Pelletier-Galarneau, Matthieu (World Journal of Nuclear Medicine, 2022)
We present the case of a 65-year-old woman with known pulmonary and muscular sarcoidosis who presented with dyspnea. FDG-PET/CT revealed unsuspected active myositis of multiple muscle groups, including the neck, and was useful in monitoring treatment response.
Keywords: sarcoidosis; myositis; PET; FDG; fluoro-deoxyglucose